2020
DOI: 10.1097/crd.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Calcium Channel Blocker: Etripamil

Abstract: Symptomatic paroxysmal cardiac arrhythmias are common cardiac conditions that lead to a decreased quality of life, increased healthcare costs, and significant morbidity. Many cardiac arrhythmias increase in frequency with age, and as the elderly population continues to increase, so will the incidence and prevalence of cardiac arrhythmias. The long-term treatment options for patients with paroxysmal arrhythmias include ablation procedures and daily oral antiarrhythmics. Acute management entails vagal maneuvers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Many cardiac arrhythmias become more frequent with advancing age, while the treatment options include interventional procedures (ablation, pacemaker implantation maze procedure) or daily oral antiarrhythmics [71]. Additionally, vagal maneuvers, intravenous antiarrhythmics, and synchronized cardioversion can be employed for acute treatment of tachyarrhythmias [72]. Oral beta-blockers and non-dihydropyridines CCBs can be self-administered as a "pill-inthe-pocket" approach for acute treatment of repeated episodes of recognized arrhythmias with an average time of 30 min or more [73].…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%
See 2 more Smart Citations
“…Many cardiac arrhythmias become more frequent with advancing age, while the treatment options include interventional procedures (ablation, pacemaker implantation maze procedure) or daily oral antiarrhythmics [71]. Additionally, vagal maneuvers, intravenous antiarrhythmics, and synchronized cardioversion can be employed for acute treatment of tachyarrhythmias [72]. Oral beta-blockers and non-dihydropyridines CCBs can be self-administered as a "pill-inthe-pocket" approach for acute treatment of repeated episodes of recognized arrhythmias with an average time of 30 min or more [73].…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%
“…Oral verapamil has been suggested as a second-line therapy for rate control in atrial fibrillation [76], cardiac extra-systolic arrhythmia alone or combined with class IC or III antiarrhythmic drugs [77]. The efficacy of IN verapamil has been tested in a dog model, while a pharmacokinetic study in rabbits revealed that the IN delivery leads to higher bioavailability compared to the oral route [72,78]. However, IN verapamil in humans resulted in almost 16.1% absolute bioavailability, attributed to dose ingestion through the nasopharynx [72,79].…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is a clear gap for a medical therapy that can provide safe, rapid, and efficacious termination of PSVT in the outpatient setting. The intranasal route is a compelling option because the posterior nasal mucosa is well suited to rapid drug absorption [ 13 ].…”
Section: Conservative Measuresmentioning
confidence: 99%
“…This leaves a relatively homogenous group, consisting of younger patients with mostly AVNRT and structurally normal hearts who are able and willing to use an intranasal medication and prefer this over tablets or ablation. It may be telling that several other intranasal therapies for cardiac conditions have been tested, such as nifedipine, nitroglycerine, and propranolol [ 13 ], and none of these are in routine use today.…”
Section: The Role Of Etripamil In Real-world Clinical Practicementioning
confidence: 99%